2016
DOI: 10.1038/srep34053
|View full text |Cite|
|
Sign up to set email alerts
|

Combinatorial nanocarrier based drug delivery approach for amalgamation of anti-tumor agents in breast cancer cells: an improved nanomedicine strategy

Abstract: Combination therapy of multiple drugs through a single system is exhibiting high therapeutic effects. We investigate nanocarrier mediated inhibitory effects of topotecan (TPT) and quercetin (QT) on triple negative breast cancer (TNBC) (MDA-MB-231) and multi drug resistant (MDR) type breast cancer cells (MCF-7) with respect to cellular uptake efficiency and therapeutic mechanisms as in vitro and in vivo. The synthesized mesoporous silica nanoparticle (MSN) pores used for loading TPT; the outer of the nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 76 publications
(88 reference statements)
3
84
0
Order By: Relevance
“…Rhodamine 123, a tracer dye which is able to enter the matrix and bind to mitochondria specifically, is widely used to detect the mitochondrial depolarization depending on the reduced fluorescence (15). The loss of ΔΨ m was assessed using FACSCalibur flow cytometry (16).…”
Section: Analysis Of Mitochondrial Membrane Potential (δψ M )mentioning
confidence: 99%
“…Rhodamine 123, a tracer dye which is able to enter the matrix and bind to mitochondria specifically, is widely used to detect the mitochondrial depolarization depending on the reduced fluorescence (15). The loss of ΔΨ m was assessed using FACSCalibur flow cytometry (16).…”
Section: Analysis Of Mitochondrial Membrane Potential (δψ M )mentioning
confidence: 99%
“…cRGD peptide has shown a strong binding toward α v β 3 integrin-overexpressed MDA-MB-231 TNBC cells. [30][31][32] Interestingly, our results showed that cRGD-MMP can effectively target to and treat MDA-MB-231 cells in vivo. This micellar mertansine prodrug (MMP) has appeared as a promising platform for potent treatment of TNBC.…”
Section: Introductionmentioning
confidence: 69%
“…3d). Rhodamine 123, which is specifically located on mitochondria, is also widely used to detect mitochondrial membrane potential based on fluorescence intensity 27 . Our results show that cells treated with MPP + caused dose-dependent decreases in the fluorescence intensity of rhodamine 123 (Fig.…”
Section: Resultsmentioning
confidence: 99%